Students’ Difficulties of Essay Writing on Virtual Learning - Muhammad Farras Rasyad; Dina Merris Maya Sari (Peneliti.net, 2020)
Essay writing with virtual learning on students’ is considered as one of the most important academic courses in a supposed program help develop students’ ability. The research subjects were 10 students’ of class 2019 A STKIP PGRI Sidoarjo English Education study program. The instrument used was a questionnaire and observation checklist. The technique for data analysis is qualitative. In analyzing essay writing data with a questionnaire and observation checklist are as follows. Taking the data questionnaire was directed using 15 questionnaires in a students’ response to learning essay writing with virtual learning with Google Form with answers to yes or no. respondents who answered yes as much 76% and then respondents who answered no as much 24%. Then got data based on observations checklist was carried out by assessing and correcting the essay writing results of 1 students’ of class 2019 A. Observe the activities carried out by lecturers and students’ virtual learning activities the results of all activities being carried out well and the class being very active even with virtual learning classes. The aim is to find out students’ difficult in essay writing with virtual learning and students’ implementation essay writing n virtual learning.